Evaluation of long-term impacts of tonsillectomy on immune functions of children: A follow-up study - Kaygusuz, Irfan; Alpay, Hayrettin Cengiz; Goedekmerdan, Ahmet; Karlidag, Turgut; Keles, Erot; Yalcin, Sinasi; Demir, Nesrin (Elsevier Ireland Ltd, 2009)
Objective: The purpose of this follow-up study was to investigate the long-term effects of tonsillectomy in comparison with their short-term results. Patients and methods: We successfully retrieved 20 out of our previously reported 37 patients who underwent tonsillectomy in our clinic 54 months ago. The blood levels of CD3+, CD4+, CD8+, CD19+, CD25+ and CD16++56+ (cellular immunity), and IgG, IgA, IgM, C3 and C4 (humoral immunity) were determined and compared with their previously reported short-term respective values. Results: There were no statistically significant differences between the short-term (1 month) and long-term (54 months) values of IgA, IgG, IgM and C4 levels of the patients (P > 0.05). There was a slight but statistically significant decrease in complement factor C3 value compared to its the early-stage value (P < 0.05) but this was not significantly different from age-matched healthy controls (P > 0.05). The Levels of CD4+ and CD19+ were higher and the Levels of CD16++56+ and CD25+ were tower in the late-stage (54 months) compared to their early-stage values (P < 0.05). When the long-term immune parameters of the tonsillectomized patients were compared with aged-match healthy controls, there were no significant differences between the levels of immunoglobulins, complements and lymphocytes (IgA, IgG, IgM, C3, C4, CD3+, CD4+, CD8+, CD19+, CD25+, CD16++56+) (P > 0.05). Conclusion: The results of this tong-term follow-up study indicate that tonsillectomy do not compromise the immune functions of children as humoral and cellular immunity of patients recovered compared to their early-stage immune status (1 month), as they have similar immune capacity compared to their age-matched healthy controls at both early- and late-stages. Although a small sample of patients enrolled, our results are of importance with respect to the reassuring in settling the widely held urban myth that tonsillectomy compromises life long immunity. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Tonsillectomy; Immune capacity; Immunoglobulin; Short-term; Long-term